New Perspectives of Corporate Identity in Sports Organizations - Josef Voráček (Karolinum Press, 2015)
This paper deals with the topic of corporate identity in sports. The main objective of this paper is to present new views, trends and tools in building a desirable image for sports organizations using corporate identity tools, including some selected areas relating to the brand. The main points of this paper include corporate design, communication, culture and sports organizations' product. These tools are all linked and transformed into the creation of a cool brand for a new generation of athletes and consumers - the so-called Generation Y of sports. This group is becoming a new economically important group for many companies in sports, as well as many sports organizations. The Sports industry is heavily dependent on the new generation of athletes in all performance levels, and sport fans. Therefore, it is necessary to constantly be innovating new corporate identity tools with a focus on the sports area.